PENGARUH EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK MINUMAN TEH KOTAK (STUDI KASUS PADA MAHASISWA PROGRAM STUDI MANAJEMEN FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS VICTORY SORONG) - Susana Magdalena Welly Muskita; Marleen Muskita (BADATI, 2021)
The main challenge that forms the basis of marketing is to build a brand or brand in the minds of consumers. Many products have low brand equity because of the many variants and substitutes that appear on the market. The box tea is also a favorite drink for students, especially students of the Management Study Program, Faculty of Economics and Business, Victory University, Sorong. The purpose of this study was to determine and analyze the effect of brand equity on the purchasing decision of boxed tea drinks (a case study of Management Study Program Students, Faculty of Economics and Business, Victory Sorong University). The research method used is quantitative research methods. The result of the research is that there is an influence of brand equity on the purchasing decision of Teh Kotak for students of the Management Study Program at Victory Sorong University. Based on the results of the calculation of the t-count value of the brand equity variable, it can be seen that the t-count value of 4.814 is smaller than the t-table value of 1.675 and the Sig value of 0.000. Thus the hypothesis is accepted, meaning that the brand equity variable has a significant influence on the decision to purchase Teh Kotak for students of the Management study program, Faculty of Economics and Business, Victory University, Sorong